1997
DOI: 10.1159/000170328
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Predilution Hemofiltration versus Ultrapure High-Flux Hemodialysis: A Multicenter Prospective Study in 23 Patients

Abstract: The aims of the present prospective multicenter study were to assess the clinical tolerance and well being, the correlation between nPCr and Kt/V and the pretreatment β2-microglobulin level in patients sequentially treated with high-flux dialysis with ultrapure bicarbonate hemodialysis (HD; phase I) and predilution hemofiltration (HF) with on-line prepared bicarbonate substitution fluid (phase II). The same monitor (Gambro AK 100 ULTRA®) and membrane (polyamide) were used. Twenty-three patients, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…This is consistent with the report of Kerr et al [11]. However, this phenomenon is in contrast to the previous observation that the use of on-line hemofiltration and high-flux membranes could achieve a comparable nPCR with a lower KT/V delivered [18,19]. As suggested Pre-ß 2 -M level = Predialysis ß 2 -microglobulin level (mg/l); pre-ß 2 -M level before HDF = predialysis ß 2 -microglobulin level before switching to on-line HDF; pre-ß 2 -M level after HDF = predialysis ß 2 -microglobulin level after switching to on-line HDF; post-ß 2 -M level = postdialysis ß 2 -microglobulin level after switching to HDF.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the report of Kerr et al [11]. However, this phenomenon is in contrast to the previous observation that the use of on-line hemofiltration and high-flux membranes could achieve a comparable nPCR with a lower KT/V delivered [18,19]. As suggested Pre-ß 2 -M level = Predialysis ß 2 -microglobulin level (mg/l); pre-ß 2 -M level before HDF = predialysis ß 2 -microglobulin level before switching to on-line HDF; pre-ß 2 -M level after HDF = predialysis ß 2 -microglobulin level after switching to on-line HDF; post-ß 2 -M level = postdialysis ß 2 -microglobulin level after switching to HDF.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it has been shown that the rate of small solute removal is less rapid during HDF than during HD, and this can influence the hemodynamic stability [25]. In addition, the potential advantages of HDF are the convective removal of medium molecules and the biocompatibility of membranes, which significantly contributes to reduction in the inflammatory processes that are implicated in dialysis morbidity and mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodiafiltration (HDF) provides solute removal over a wide molecular weight range [1] and is considered a suitable dialysis technique for patients with a poor cardiovascular stability [2,3]. As compared with conventional hemodialysis (HD), it is associated with a lower morbidity [4], an improvement of uremic neuropathy, and a lower incidence of carpal tunnel syndrome and joint pain [5][6][7].…”
Section: Introductionmentioning
confidence: 99%